2017
DOI: 10.1186/s40168-017-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut symbiont enhances insecticide resistance in a significant pest, the oriental fruit fly Bactrocera dorsalis (Hendel)

Abstract: BackgroundSymbiotic bacteria affect insect physiology and ecology. They may also mediate insecticide resistance within their hosts and thereby impact pest and vector control practices. Here, we document a novel mechanism of insecticide resistance in which a gut symbiont of the tephritid pest fruit fly Bactrocera dorsalis enhances resistance to the organophosphate insecticide trichlorphon.ResultsWe demonstrated that the gut symbiont Citrobacter sp. (CF-BD) plays a key role in the degradation of trichlorphon. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
288
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(317 citation statements)
references
References 63 publications
6
288
1
1
Order By: Relevance
“…There is growing evidence to support the involvement of insect‐associated bacterial symbionts in detoxification of chemical insecticides, e.g. the stink bug R. pedestri and its symbiont Burkholderia spp., the diamondback moth ( Plutella xylostella L.) and the symbionts Bacillus , Enterobacter and Pantoea spp., and the fruit fly ( Bactrocera dorsalis Hendel) with associated Citrobacter spp . These bacteria are mainly associated with the detoxification of organophosphates, although Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence to support the involvement of insect‐associated bacterial symbionts in detoxification of chemical insecticides, e.g. the stink bug R. pedestri and its symbiont Burkholderia spp., the diamondback moth ( Plutella xylostella L.) and the symbionts Bacillus , Enterobacter and Pantoea spp., and the fruit fly ( Bactrocera dorsalis Hendel) with associated Citrobacter spp . These bacteria are mainly associated with the detoxification of organophosphates, although Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are mainly associated with the detoxification of organophosphates, although Bacillus spp. can also detoxify oxadiazine insecticides …”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that B. dorsalis adults were attracted by the metabolites of symbiotic Enterobacteriaceae (Shi, Wang, & Zhang, ). Recently, a study demonstrated that Enterobacteriaceae can degrade trichlorphon and increase the insecticide resistance of host (Cheng et al., ). The continuous presence and dominance of the Enterobacteriaceae family in the gut bacterial community of tephritidae fruit flies indicate an important functional role as symbionts in host fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Current research on insect–microbe symbioses has revealed both mutualistic and antagonistic relationships between insect hosts and their microbial symbionts . In a mutualistic relationship, the microbial symbiont improves the ecological fitness of its insect host . In an antagonistic relationship, the microbial symbiont threatens the survival of the insect host.…”
Section: Introductionmentioning
confidence: 99%